Influx of meltwater subglacial Lake Concordia, East Antarctica - A. A. Tikku; R. E. Bell; M. Studinger; G. K. C. Clarke; F. Ferraccioli; I. Tabacco (International Glaciological Society, 2005)
We present evidence for melting at the base of the ice that overlies Lake Concordia, an 800 km(2) subglacial lake near Dome Concordia, East Antarctica, via a combination of glaciohydraulic melting (associated with the tilted ice ceiling and its influence on lake circulation/melting temperature) and melting by extreme strain heating (where the ice sheet is grounded). An influx of water is necessary to provide nutrients, material and biota to support subglacial lake ecosystems but has not been detected previously. Freezing is the dominant observed basal process at over 60% of the surface area above the lake. The total volume of accreted ice above the lake surface is estimated as 50-60 km(3), roughly 25-30% of the 200 +/- 40 km(3) estimated lake volume. Estimated rates of melting and freezing are very similar, +/- 2-6 mm a(-1). The apparent net freezing may reflect the present-day response of Lake Concordia to cooling associated with the Last Glacial Maximum, or a large influx of water either via a subglacial hydrological system or from additional melting of the ice sheet. Lake Concordia is an excellent candidate for subglacial exploration given active basal processes, proximity to the Dome Concordia ice core and traverse resupply route.